2023
DOI: 10.3390/cancers15225346
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Interaction between Proton Pump Inhibitors and Cancer Treatment

Hao Chen,
Masaaki Kondo,
Nobuyuki Horita
et al.

Abstract: We have read the article authored by Rizzo et al [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies have explored the impact of PPIs usage on the efficacy and safety of EGFR-TKIs in NSCLC patients, and reported a reduction in the effectiveness of EGFR-TKIs with shorter PFS and OS. 32,33 Our study found that 41.9% NSCLC patients had concomitant use of afatinib and PPIs. The proportion of patients receiving the coadministration of afatinib and PPIs was not significantly different between the PFS > 36 months group and the PFS ≤36 months group (45.2% vs. 41.3%; p = 0.506).…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have explored the impact of PPIs usage on the efficacy and safety of EGFR-TKIs in NSCLC patients, and reported a reduction in the effectiveness of EGFR-TKIs with shorter PFS and OS. 32,33 Our study found that 41.9% NSCLC patients had concomitant use of afatinib and PPIs. The proportion of patients receiving the coadministration of afatinib and PPIs was not significantly different between the PFS > 36 months group and the PFS ≤36 months group (45.2% vs. 41.3%; p = 0.506).…”
Section: Discussionmentioning
confidence: 74%